Pengembangan Sistem Inventori Dengan Metode Trend Moment Untuk Optimalisasi Persediaan Gudang Menggunakan Teknologi RFID - Rusito Rusito; Muhammad Fathony (JURIKOM (Jurnal Riset Komputer), 2019)
Today's technology is still developing rapidly and creating innovations and the latest works. One of them is Radio Frequency Identification (RFID) technology. The Trend Moment method in value has advantages over other methods, namely the use of parameter X or historical data. This is because the values in parameter X always start with the value 0 as the first order and there are no even or odd data differences. Of the problems that exist, there is a need for optimizing the stock using the Trent Moment Method with web-based and using RFID technology. This system includes controlling inventory at the warehouse for purchases, thereby reducing excess or insufficient stock so that inventory inventory is controlled, as well as data input processes that utilize RFID, thus speeding up the time in the data input process. This system uses PHP and MYSQL programming languages as a database and utilizes the PHP Framework namely Codeigniter in making this website. With the web-based system, making it easy for employees to process data in a timely manner. The results of the study stated that the Inventory System With the Trend Moment Method by experts obtained an average value of 3.7 included in the very valid category and validation of the user obtained an average of 87.5% included in the very valid category. The Inventory System Application with the Trend Moment Method regulates the ordering of components for warehouse inventory.